SQL query expressed in relational calculus - Thuần, Hồ; Thành, Trần Thiên (Journal of Computer Science and Cybernetics, 2016)
In this paper, we present some results on the equivalence between SQL queries and relation calculus expressions. These results are used to translate SQL queries into equivalent expressions of relational algebra.